Adaptação cultural do instrumento Geriatric Institutional Assessment Profile (GIAP) para o contexto cultural brasileiro - Mágda Carla de Oliveira Souza e Silva (2015)
In view of the inevitability of population aging, it is a matter of urgency to innovate and change the paradigms of health care to the elderly. In order to meet this requirement, evaluation mechanisms of assistance to the elderly should be in place as one of the fundamental aspects to improve the effectiveness of geriatric care. For that purpose, the Nurses Improving Care for Healthsystem Elders (NICHE) program has developed the Institutional Geriatric Assessment Profile (GIAP). This scale features 213 items split into 25 questions and 3 major scales built to assess the knowledge about the institutional policies, institutional barriers to the best practice, conflicts over the proper care, clinical knowledge, perceived responsibility for the inadequate practice and perceptions of complementarity in the workplace. Objective: Development of the cultural adaptation of the GIAP instrument to the reality of nurses in charge of the elderly care in Brazilian hospitals. Methodology: The process of cultural adaptation of the GIAP instrument followed the guidelines of Beaton et al. (2000). The following steps were taken: translation of the GIAP instrument into Portuguese, synthesis of translations, back-translation of the synthetic version, synthesis of the back-translations, review by an expert committee, and back-translation of the adapted version. The concurrence among the specialists was calculated through the Content Validity Index (CVI). The study was carried out from January through June 2015. Results: The GIAP instrument was translated independently by two translators, originating two translations (T1 and T2) that were subjected to analysis and synthesis; the outcome was the version T12. This version was back-translated by two other translators. The RT1 and RT2 versions were then compared to one another and resulted in the RT12 synthetic version. This version was submitted to a reviewer who considered that the back-translation RT12 is equivalent to the original document. At the stage of appraisal by the Panel of Judges the version T12 was reviewed five times by ten experts until it reached a consistency greater than 80.0% on each item, what generated the final synthesis version T17 with an overall CVI of 93.9. This adapted version was back-translated into the GIAPs original language. The original and the adapted documents were considered equivalent by the back-translator. The face validity of the instrument showed that it meets the proposed objectives (CVI of 100.0%), features suitable structure and presentation (CVI of 94.0%) and is relevant to the topic at hand (CVI of 100.0%). Conclusion: Contributions forwarded by all translators, reviewers and experts were fundamental for the instruments semantic, idiomatic, conceptual and experiential equivalence, including adequate content and face validity. The process of cross-cultural adaptation is the first step for the GIAP to become available for application in another cultural context. Further analysis of the instrument acceptability and assessment of its psychometric properties are still necessary for the GIAP to be deemed suitable for use in the Brazilian context.